Implementasi Pemberdayaan Pengawas terhadap Efektivitas Supervisi Pengawas Pendidikan Agama Islam - Sufiani, Sufiani; Putra, Aris Try Andreas (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2020)
This paper presents the finding of qualitative study aiming to describe the implementation of supervisor empowerment to the effectiveness of supervision of Islamic education supervisors at Southeast Sulawesi, Indonesia. The data were collected from observation, interviews, and documentation. The findings indicate that the supervisors of Islamic education have been well empowered through the implementation of trust, authority, encouragement, and responsibilities. They have been well empowered through trust, power, encouragement and implementation of responsibilities. They can perform their main duties, authority, and responsibilities effectively through assisting teacher, assisting and assessing teachers’ administration, as well as assisting and assessing teachers’ academic.